Educación ambiental para la conciencia ambiental en estudiantes de la Unidad Educativa Mater Misericordiae, Calceta cantón Bolívar - Hurtado Bustamante, Tania Yadira (2021)
The present investigation consisted of evaluating the incidence of environmental education on environmental awareness in students of the Mater Misericordiae Educational Unit, Bolívar canton. An initial environmental awareness diagnosis in its 4 dimensions was applied to the students; affective, cognitive, dispositional and active, divided into 4 levels; favorable, very favorable, unfavorable and very unfavorable, in each dimension unfavorable values predominate over favorable values; in the affective dimension 53.57% unfavorable and 35.71% very unfavorable, in the cognitive dimension 42.86% very unfavorable and 39.29% unfavorable, in the dispositional dimension 64.29% unfavorable and 7.14% very unfavorable in the active dimension, 57.14% unfavorable and 7.14% very unfavorable. Taking into account the initial diagnosis, an environmental education strategy was applied, which was chosen according to the preferences of the students, which consists of learning objectives such as making children aware of environmental problems. Based on the topics learned, final diagnoses were made where the students show 83.33% of achievements in environmental knowledge and 80% of achievements in environmental behavior, also in environmental awareness the students showed progress in the affective dimension 75% very favorable and 25% favorable, in the cognitive dimension 53.57% favorable and 46.4% very favorable, in the dispositional dimension 67.9% favorable and 32.1% very favorable and in the active dimension 57.1% favorable and 42.9% very favorable.